PERBEDAAN HASIL MENGHIAS KUKU (NAIL ART) 3 DIMENSI BENTUK BUNGA MENGGUNAKAN ACRYLIC POWDER DENGAN CARVING GEL - Ariani, Fauziah; Okatini, Mari; Atmanto, Dwi (Jurnal Socia Akademika, 2024)
This objective of study to find out the difference between the three-dimensional nail art result between the use of acrylic powder and carving gel. This type of research is quantitative descriptive with experimental methods. The population used in this study was active students of the 2020 Army Cosmetics and Beauty Studies Program, Jakarta State University who had no disease or nail abnormalities. Sampling techniques using purposive sampling. The method of data collection in this study is an observation method, carried out with instruments in the form of a sheet of criteria of evaluation in the shape of an eclipse. The study uses indicators of evaluation such as texture, design suitability, versatility, and preference level. The panellists in this study were three people. Data analysis techniques using normality test, homogenity test and t-test based on the results of the hypothesis showed that there was a difference in nail art results between using acrylic powder and carving gel. This is demonstrated by the calculations obtained by thitung > ttable is 3,214 > 2,306, then Ho rejected at the level of significance 0,05.